Correction: Prefrontal GABA levels, hippocampal resting perfusion and the risk of psychosis. (December 2018) - Modinos, Gemma; Şimşek, Fatma; Azis, Matilda; Bossong, Matthijs; Bonoldi, Ilaria; Samson, Carly; Quinn, Beverly; Perez, Jesus; Broome, Matthew; Zelaya, Fernando; Lythgoe, David; Howes, Oliver; et al.
This article was originally published under NPG's License to Publish, but has now been made available under a [CC BY 4.0] license. The PDF and HTML versions of the paper have been modified accordingly.